6th DACH+ Conference on Energy Informatics (EnInf 2017) - Santini, Silvia; Tiefenbeck, Verena (Computer Science - Research and Development, 2018)

A Field Experiment on Biases in Food Waste Measurement Methods - Merian, Sybilla; O'Sullivan, Kevin; Stoeckli, S. J.; Beretta, C.; Tiefenbeck, Verena; Mueller, N.; Fleisch, Elgar; Natter, M. (Proceedings of the European Marketing Academy, 2023)
Reducing consumer food waste is currently on many national agendas. Despite the urgency of the issue, there is a lack of accurate measurement methods, making it difficult to quantify con-sumer food waste and identify effective interventions. Accurate measurement requires a deep understanding of how measurement methods are biased. In a field experiment with 369 house-holds, we analyzed biases associated with different measurement methods (survey, diary, kitchen caddy) and procedures. Results allow us to quantify how different measurement meth-ods deviate from each other and how biases impair reported and measured food waste esti-mates. Survey-based underreporting seems difficult to avoid, even when combined with other methods. Households’ awareness of food waste can only partially explain this. The analysis further suggests that results are affected by an Experimenter Demand Effect. Based on the in-sights generated, we discuss ideas for the improvement of measurement methods.<br

A field experiment to assess barriers to accurate household food waste measurements - Merian, Sybilla; O'Sullivan, Kevin; Stöckli, Sabrina; Beretta, Claudio; Müller, Nadina; Tiefenbeck, Verena; Fleisch, Elgar; Natter, Martin (Resources Conservation and Recycling, 2024)
The United Nations’ sustainable development goals call for a 50 % reduction in global household food waste by 2030, but an accurate measurement method to quantify household food waste has yet to be developed. In a field experiment with 359 households, this study compares standard food waste measurement methods (survey, diary, kitchen caddy) and assesses the barriers to accurate measures. Based on our experimental design, we derive a minimal estimate of food waste (ground truth) that allows us to examine and explain the differences in the results of these methods. The results suggest that physical waste measurement is the most accurate measurement method, as it evokes the least behavioral adaptations. However, this method is resource-intensive and not always feasible. We provide guidance on how to measure food waste based on the purpose of the measurement, including specific materials to use and reporting standards to follow.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Biases; Diary; Household food waste measurement; Kitchen caddy; Survey; Underestimation

Aggregation effects for microgrid communities at varying sizes and prosumer‐consumer ratios - Griego, Danielle; Schopfer, Sandro; Henze, Gregor; Fleisch, Elgar; Tiefenbeck, Verena (Energy Procedia, 2019)
Self-consumption is an increasingly economically attractive solution for electricity generated by distributed energy resources, which also reduces transmission losses, power line overload and grid instability. Yet, at single-building scale, production and demand do often not coincide. Microgrids are proposed as a means to trade surplus energy produced with local prosumers and consumers, to take advantage of complementary load profiles. Here we define a consumer as a single metered residential unit, a prosumer as a consumer with a photovoltaic system, which first uses the on-site energy generated prior to exporting the surplus, and the microgrid as a clearly defined number of both prosumers and consumers. In this article, we systematically analyze to what extent varying microgrid sizes and prosumer-consumer ratios affect local self-consumption and self-sufficiency rates. To that end, we developed a simulation model that uses real-world load profiles from 4190 residential buildings as input data. We find that the prosumer-to-consumer ratio is more important than the absolute microgrid size, for microgrids sizes greater than ten. The results also indicate that prosumer-to-consumer ratios in the range of 40%-60% have the best performance. Each simulation is also compared to the baseline scenario of a stand-alone prosumer, which shows significantly better self-consumption ratios and self-sufficiency ratios for microgrids due to aggregation effects. Finally, this work may also be used as a reference to design residential microgrid communities for various prosumer-consumer compositions and various production-to-demand ratios.<br
Keywords: Microgrids; self-consumption; self-sufficiency; prosumers; aggregation effects

Better get focused: How feedback on a specific behavior can reduce energy consumption - Tiefenbeck, Verena; Götte, Lorenz; Schöb, Samuel; Staake, Thorsten (International Energy Policy & Programme Evaluation Conference (IEPPEC 2016), 2016)

Bidding on a Peer-to-Peer Energy Market: An Exploratory Field Study - Wörner, Anselma; Tiefenbeck, Verena; Wortmann, Felix; Meeuw, Arne; Ableitner, Liliane; Fleisch, Elgar; Azevedo, Inês (Information Systems Research, 2022)
Moving toward sustainable energy systems to address climate change is one of the key challenges of our generation. To that end, investments in renewable energy and balancing renewable supply and energy demand on the larger scale are crucial. One mechanism to create price signals for demand balancing, as well as for consumer engagement, is to establish trading platforms (or peer-to-peer (P2P) markets) through which households can directly buy and sell renewable energy. However, residential consumers are typically lay users with little or no previous exposure to the complexity and the dynamics involved in energy markets. More so, empirical research on consumer engagement in the energy sector indicates that individuals tend to act against their stated proenvironmental intentions and to lose interest in energy management systems particularly quickly—calling into question regulatory efforts to foster P2P markets to push the transition to renewable energy. We have implemented the first empirical study worldwide that analyzes bidding behavior in a real-world P2P energy market, in which users bid for solar energy via an auction mechanism. For the duration of an entire year, users could interact with the market using a web app. The prices settled on the P2P market directly impacted participants’ electricity bills. We provide unique empirical evidence showing that (1) participants were willing to engage in energy trading and that (2) they understood the market mechanism surprisingly well and exhibited learning effects. Still, bidding behavior did not reflect their stated intention of paying a price premium for local solar energy. The market outcomes reveal that P2P energy markets can indeed have a positive impact on balancing demand and supply, thereby addressing the fundamental challenge of distributed renewable energy systems.<br
Keywords: green IS; P2P markets; electronic markets; market design; sustainable energy systems

Blockchain-enabled markets: A literature review with a focus on decentralised energy markets - Wörner, Anselma; Tiefenbeck, Verena; Ketter, Wolfgang (Edward Elgar Publishing Ltd., 2023)
CRIS-Team Scopus Importer:2024-12-16

Bring behaviour into the digital transformation - Tiefenbeck, Verena (Nature Energy, 2017)

Chapter 16: Blockchain-enabled markets: A literature review - Wörner, Anselma; Tiefenbeck, Verena; Ketter, Wolfgang (Handbook of Information Systems and the Environment, 2023)
This comprehensive Research Handbook provides international perspectives on the role of information systems in environmental sustainability, drawing on ground-breaking research from leading scholars to predict future trends. Presenting in-depth studies which utilise a diverse range of research approaches and methods, this insightful Handbook provides a thorough examination of information systems research on environmental sustainability.<br
Keywords: Sustainable Information Systems; Green Information Systems; Energy Informatics; Pro-environmental Mindset and Behaviour; Digital transformation for sustainable markets and economies; Green Information Technology

Complementarities in behavioral interventions: Evidence from a field experiment on resource conservation - Fang, Ximeng; Götte, Lorenz; Rockenbach, Bettina; Tiefenbeck, Verena; Sutter, Matthias; Schöb, Samuel; Staake, Thorsten (Journal of Public Economics, 2023)
Behavioral policy often aims at influencing behavior by mitigating biases due to, e.g., imperfect information or inattention. We study how this is affected by the simultaneous presence of multiple biases arising from different sources, through a field experiment on resource conservation in an energy- and water-intensive everyday activity (showering). One intervention, shower energy reports, primarily targeted knowledge about environmental impacts; another intervention, real-time feedback, primarily targeted salience of resource use. We find a striking complementarity. While only the latter induced significant conservation effects when implemented in isolation, each intervention became more effective when implemented jointly. This is consistent with predictions from a theoretical framework that highlights the importance of targeting all relevant sources of bias to achieve behavioral change.<br

Eco-feedback interventions: selective attention and actual behavior change - Ableitner, Liliane; Tiefenbeck, Verena; Fleisch, Elgar; Staake, Thorsten (Americas Conference on Information Systems (AMCIS 2016), 2018)
The right information can foster behavior change towards energy conservation – given that the receiving individuals pay attention to the feedback provided and integrate the information in their decision making. As human information processing capabilities are limited, intervention designers need to choose content carefully to avoid information overload. Based on energy consumption and survey data collected in field trial, this article investigates the attention paid to different elements of the user interface (N=426) and establishes a relationship to actual energy conservation. We find that self-reported attention paid to content explains only very little of the measured behavior change (explanatory power of approx. 3%). The article is a first step towards better understanding the black box of feedback interventions in the energy sector. The results highlight the importance of collecting real-world data on behavior – rather than relying on self-reported user perceptions – in the resource consumption context and beyond.<br

Economic assessment of photovoltaic battery systems based on household load profiles - Schopfer, Sandro; Tiefenbeck, Verena; Staake, Thorsten (Applied Energy, 2018)
Technical advances and decreasing costs of photovoltaic (PV) and battery (B) systems are key drivers for the consumer-prosumer transition in many countries. However, the installation of a photovoltaic-battery (PVB) system is not equally profitable for all consumers. This study systematically assesses how heterogeneity in real-world electricity load profiles affects the optimal system configuration and profitability of PVB systems. To that end, we develop a techno-economic simulation model that optimizes the PVB configuration for given electricity load profiles. The analysis uses real-world energy consumption data from 4190 households and is conducted for current electricity rates and weather conditions in Zurich, Switzerland. To account for future price reductions of PV and PVB systems, we conduct a sensitivity analysis that assesses how different cost scenarios influence optimal system configuration and profitability. Finally, we develop and validate a machine learning algorithm that can predict system profitability based only on a limited set of features and on shorter measurement timeframes of smart-meter data. We find that under the current cost scenario (PV: 2000 €/kWp, B: 1000 €/kWh) and without subsidies, about 40% of the analyzed households reach a positive net present value (NPV) for a PV-system, but only for 0.1% of households is the integration of a battery profitable. Under the most optimistic cost scenario for both technologies (PV: 1000 €/kWp, B: 250 €/kWh), 99.9% of the households benefit from the integration of battery storage into their optimal system configuration, with a mean installed PV power of 4.4 kWp and a mean battery size of 9.6 kWh. In all cost scenarios, system profitability varies considerably between households, even for households with comparable total annual demand, primarily due to the heterogeneity in the load profiles. Thus, being able to identify households for whom the installation is profitable is important. The proposed machine learning algorithm predicts optimal configuration, profitability, self-sufficiency, and self-sufficiency ratios with good accuracy, even when only relatively short timeframes of smart-meter data are available. The results of this study are relevant for households making individual investment decisions as well as for utility companies to more effectively identify and approach relevant customers for the installation of PVB systems. Furthermore, the findings enable policymakers to determine the critical levers for increasing private investments into PVB systems in their region and to predict how future developments like component costs will affect the future diffusion of these systems.<br

Effect of tariff arbitrage on photovoltaic battery economics using predictive control - Schopfer, Sandro; Tiefenbeck, Verena; Fleisch, Elgar; Staake, Thorsten (International Conference on Energy, Environment and Economics (ICEEE 2016), 2016)

Effects of Digital Food Labels on Healthy Food Choices in Online Grocery Shopping - Fuchs, Klaus; Lian, Jie; Michels, Leonard; Mayer, Simon; Toniato, Enrico; Tiefenbeck, Verena (Nutrients, 2022)
In order to induce the shift in consumer behavior necessary for the mitigation of diet-related diseases, front-of-package labels (FoPL) such as the Nutri-Score that support consumers in their efforts to identify nutritionally valuable products during grocery shopping have been found to be effective; however, they remain non-compulsory in most regions. Counter-intuitively, a similar stream of research on digital web-based FoPL does not yet exist, even though such digital labels hold several advantages over physical labels. Digital FoPL can provide scalable and personalized interventions, are easier to implement than physical labels, and are especially timely due to the recent increase in online grocery shopping. The goal of this study was to demonstrate the technical feasibility and intervention potential of novel, scalable, and passively triggered health behavior interventions distributed via easy-to-install web browser extensions designed to support healthy food choices via the inclusion of digital FoPL in online supermarkets. To that end, we developed a Chrome web browser extension for a real online supermarket and evaluated the effect of this digital food label intervention (i.e., display of the Nutri-Score next to visible products) on the nutritional quality of individuals’ weekly grocery shopping in a randomized controlled laboratory trial (N = 135). Compared to the control group, individuals exposed to the intervention chose products with a higher nutritional quality (e.g., 8% higher healthy trolley index (HETI), 3.3% less sugar, 7.5% less saturated fat). In particular, users with low food literacy seemed to benefit from the digital FoPL (e.g., 11% higher HETI, 10.5% less sugar, 5.5% less saturated fat). Furthermore, participants exposed to the food label advocated its introduction more strongly than the control group (p = 0.081). Consumers worldwide could easily install such applications to display digital food labels on their end devices, and would thus not have to wait for stakeholders in the food industry to eventually reach consensus on mandatory food label introduction.<br
Keywords: Nutri-Score; digital food labels; food choice; randomized controlled trial (RCT)

Empowering Consumers to Make Environmentally Sustainable Online Shopping Decisions: A Digital Nudging Approach - Michels, Leonard; Ochmann, Jessica; Günther, Sebastian A.; Laumer, Sven; Tiefenbeck, Verena (HICSS 2022, 2022)

Energy conservation: Real-time feedback reduces energy consumption among the broader public without financial incentives - Tiefenbeck, Verena; Wörner, Anselma; Schöb, Samuel; Fleisch, Elgar; Staake, Thorsten (Nature Energy, 2019)

For better or for worse? Empirical evidence of moral licensing in a behavioral energy conservation campaign - Tiefenbeck, Verena; Staake, Thorsten; Roth, Kurt; Sachs, Olga (Energy Policy, 2013)
Isolated environmental campaigns focusing on defined target behaviors are rolled out to millions of households every year. Yet it is still unclear whether these programs trigger cross-domain adoption of additional environment-friendly behaviors (positive spillover) or reduced engagement elsewhere. A thorough evaluation of the real net performance of these programs is lacking. This paper investigates whether positive or perverse side effects dominate by exemplifying the impact of a water conservation campaign on electricity consumption. The study draws on daily water (10,780 data points) and weekly electricity (1386 data points) consumption data of 154 apartments in a controlled field experiment at a multifamily residence. The results show that residents who received weekly feedback on their water consumption lowered their water use (6.0% on average), but at the same time increased their electricity consumption by 5.6% compared with control subjects. Income effects can be excluded. While follow-up research is needed on the precise mechanism of the psychological process at work, the findings are consistent with the concept of moral licensing, which can more than offset the benefits of focused energy efficiency campaigns, at least in the short-term. We advocate the adoption of a more comprehensive view in environmental program design/evaluation in order to quantify and mitigate these unintended effects.<br

Greener or Faster: Unraveling the Impact of Travel Time Presentation on Rail vs. Air Travel Decision-Making - Kuhlemann, Sophie; Mehta, Prakhar; Tiefenbeck, Verena (International Conference on Information Systems (ICIS) 2024, 2024)

How far along are local energy markets in the DACH+ region? A comparative market engineering approach - Weinhardt, Christof; Mengelkamp, Esther; Cramer, Wilhelm; Hambridge, Sarah; Hobert, Alexander; Kremers, Enrique; Otter, Wolfgang; Pinson, Pierre; Tiefenbeck, Verena; Zade, Michel (2019 ACM e-Energy Workshop on Market Engineering (2019 e-Energy EME Workshop), 2019)
Local energy markets (LEMs) allow localized energy trading between actors within a community. Academic research has actively investigated the LEM concept to support the European energy transition since the turn of the millennium. However, the actual implementation of LEMs in real-life projects has only begun in 2016. We provide a market engineering comparison of the currently most developed LEM projects in the DACH+ region, analyzing and comparing nine LEM implementation projects. So far, LEM projects are in the early stages of development, e. g. proof-of-concept stage, and focus on electricity trading between few residential participants. Regulatory obstacles are evident in all project

Implementing a blockchain-based local energy market: Insights on communication and scalability - Meeuw, Arne; Schopfer, Sandro; Wörner, Anselma; Ableitner, Liliane; Tiefenbeck, Verena; Fleisch, Elgar; Wortmann, Felix (Computer Communications, 2020)
Peer-to-peer (P2P) energy markets are gaining interest in the energy sector as a means to increase the share of decentralised energy resources (DER), thus fostering a clean, resilient and decentralised supply of energy. Various reports have touted P2P energy markets as ideal use case for blockchain-technology, as it offers advantages such as fault-tolerant operation, trust delegation, immutability, transparency, resilience, and automation. However, relatively little is known about the influence of hardware and communication infrastructure limitations on blockchain systems in real-life applications. In this article, we demonstrate the implementation of a real-world blockchain managed microgrid in Walenstadt, Switzerland. The 37 participating households are equipped with 75 special smart-metres that include single board computers (SBC) that run their own, application-specific private blockchain. Using the field-test setup, we provide an empirical evaluation of the feasibility of a Byzantine fault tolerant blockchain system. Furthermore, we artificially throttle bandwidth between nodes to simulate how the bandwidth of communication infrastructure impacts its performance. We find that communication networks with a bandwidth smaller than 1000 kbit/s – which includes WPAN, LoRa, narrowband IoT, and narrowband PLC – lead to insufficient throughput of the operation of a blockchain-managed microgrid. While larger numbers of validators may provide higher decentralisation and fault-tolerant operation, they considerably reduce throughput. The results from the field-test in the Walenstadt microgrid show that the blockchain running on the smart-metre SBCs can provide a maximum throughput of 10 transactions per second. The blockchain throughput halts almost entirely if the system is run by more than 40 validators. Based on the field test, we provide simplified guidelines for utilities or grid operators interested in implementing local P2P markets based on BFT systems.<br
Keywords: Local energy markets; Peer-to-peer trading; Blockchain managed microgrid; Smart grid communication; Network requirements

Information Systems and Behavioural Change: Feedback Interventions to curb the consumption of natural resources - Staake, Thorsten; Tiefenbeck, Verena; Stiefmeier, Thomas (Handbook of Information Systems and the Environment, 2023)
This comprehensive Research Handbook provides international perspectives on the role of information systems in environmental sustainability, drawing on ground-breaking research from leading scholars to predict future trends. Presenting in-depth studies which utilise a diverse range of research approaches and methods, this insightful Handbook provides a thorough examination of information systems research on environmental sustainability.<br
Keywords: Sustainable Information Systems; Green Information Systems; Energy Informatics; Pro-environmental Mindset and Behaviour; Digital transformation for sustainable markets and economies; Green Information Technology

Integration of prosumer peer-to-peer trading decisions into energy community modelling - Pena-Bello, Alejandro; Parra, David; Herberz, Mario; Tiefenbeck, Verena; Patel, Martin K.; Hahnel, Ulf J. J. (Nature Energy, 2021)
Peer-to-peer energy trading can foster participation in the energy transition, but little is understood about prosumer preferences and their effect on the grid. Pena-Bello et al. use an online experiment among German homeowners to study decision-making strategies and simulate their impact on the operation of an energy community.
CRIS-Team WoS Importer:2021-12-24

Is It All About Transparency? The Effectiveness and Ethics of a Digital Salience Nudge - Michels, Leonard; Schmitt, Kathrin; Ochmann, Jessica; Laumer, Sven; Tiefenbeck, Verena (Proceedings of the 2021 European Conference on Information Systems, 2021)

Long-lasting effects or short-term spark? On the persistence of behaviour change induced by real-time feedback on resource consumption - Tiefenbeck, Verena; Tasic, Vojkan; Schöb, Samuel; Staake, Thorsten (European Conference on Information Systems (ECIS 2016), 2016)
In the promotion of sustainable consumer behaviour, it is important to establish a mental relation between one’s behaviour and its environmental impact. High hopes rest on timely feedback on personal energy consumption in order to create this link. Great efforts are being put into the development of information systems to achieve this, and smart meters are being deployed as an enabling technology worldwide. Recent smart metering trials, which provide feedback on aggregate household electricity consumption, report moderate savings of 2-5%. There is, however, a vivid controversy about consumer interest and continuous use of these technologies in the long run. This uncertainty introduces substantial risk to the deployment of these technologies, as the persistence of savings is crucial for the cost-benefit analyses and scalability of these programs. This paper investigates the long-term stability of the behaviour change induced by a real-time feedback technology. Our initial study found average energy savings of 22% for the target behaviour. In this study, we analyse 17,612 data points collected in a one-year follow-up field study. The results suggest that the effects of behaviour-specific feedback on energy consumption do not exhibit a significant decay, indicating that this kind of technology successfully induces persistent behaviour change.<br

Mechatronics to drive environmental sustainability: Measuring, visualizing, and transforming consumer patterns on a large scale - Tiefenbeck, Verena; Tasic, Vojkan; Schöb, Samuel; Staake, Thorsten (39th Annual Conference of the IEEE Industrial Electronics Society (IECON 2013), 2013)
In order to reduce our society's dependence on fossil fuels, the energy sector has started to undergo massive changes. Information and communications technology (ICT) increasingly plays a key role in this transformation, both on the supply and demand side. While 85% of the residential energy in the DACH region is consumed by space and water heating, the vast majority of work in the energy informatics field does not focus on these two critical end uses. And yet, the discipline could contribute greatly to reducing consumption and emissions in this area - often with a close nexus to electricity. Besides, direct, real-time feedback on hot water consumption has a particularly high savings potential and can further broaden the sphere of impact of the energy informatics discipline. This paper describes a self-powered energy and water meter that provides users with such feedback in the shower. After an earlier proof of concept study with 60 households together with the Swiss Federal Office of Energy that yielded average energy and water savings of 22%, the smart shower meter has been developed into a mass-market compatible application that has been installed in 8,000 households. This was accompanied by a study with 700 households to verify its practical viability, consumer engagement, and effectiveness in the field. The device showcases a practical example of how ICT applications can be successfully implemented at scale to transform consumption patterns in emission-intense domains, also beyond electricity.<br

On the magnitude and persistence of the Hawthorne effect - evidence from four field studies - Tiefenbeck, Verena (4th European Conference on Behaviour and Energy Efficiency (Behave 2016), 2016)
Participants of research studies may exhibit altered behaviour resulting from awareness of being a part of an experimental study. Although this so-called Hawthorne effect has led to increased scrutiny in social science research, little is still known about the magnitude and persistence of that phenomenon. The findings of several recent field studies on resource conservation indicate the occurrence of substantial Hawthorne effects. This raises concerns that even robust studies with treatment and control may not sufficiently disentangle Hawthorne effects from participants’ actual response to the intervention, casting doubts on the treatment effects reported and on the generalizability of the findings to non-study populations. In this article, we seek to gauge the magnitude and time dynamics of the Hawthorne effect. We analyse the behaviour of the control groups in four independent randomized controlled trials on resource conservation conducted in Switzerland, the Netherlands, and Singapore. Each study comprised between 525 and 800 households and collected detailed measurement data on participants’ energy and water use over two to six months. We find strikingly consistent patterns across the four studies: each control group initially increased their resource use and transitioned within the first few weeks into a relatively stable level of consumption, 5-20 percent above the initial level. Our interpretation is that control group households reduced their resource use at the beginning of the study compared to their pre-study behaviour, yet relapsed towards their pre-study behaviour as they got used to the measurement device. We can rule out seasonal trends as an alternative explanation and attribute these patterns to Hawthorne or salience effects. Our data suggest that the current practice of collecting baseline data at the beginning of studies may lead to biased reference points, as the baseline coincides with the period most affected by the Hawthorne effect.<br

Overcoming salience bias: How real-time feedback fosters resource conservation - Tiefenbeck, Verena; Götte, Lorenz; Degen, Kathrin; Tasic, Vojkan; Fleisch, Elgar; Lalive, Rafael; Staake, Thorsten (Management Science, 2018)
Inattention and imperfect information bias behavior toward the salient and immediately visible. This distortion creates costs for individuals, the organizations in which they work, and society at large. We show that an effective way to overcome this bias is by making the implications of one’s behavior salient in real time, while individuals can directly adapt. In a large-scale field experiment, we gave participants real-time feedback on the resource consumption of a daily, energy-intensive activity (showering). We find that real-time feedback reduced resource consumption for the target behavior by 22%. At the household level, this led to much larger conservation gains in absolute terms than conventional policy interventions that provide aggregate feedback on resource use. High baseline users displayed a larger conservation effect, in line with the notion that real-time feedback helps eliminate “slack” in resource use. The approach is cost effective, is technically applicable to the vast majority of households, and generated savings of 1.2 kWh per day and household, which exceeds the average energy use for lighting. The intervention also shows how digitalization in our everyday lives makes information available that can help individuals overcome salience bias and act more in line with their preferences.<br

Peak load minimization of an e-bus depot: impacts of user-set conditions in optimization algorithms - Toniato, Enrico; Mehta, Prakhar; Marinkovic, Stevan; Tiefenbeck, Verena (Energy Informatics, 2021)
The transport sector is responsible for 25% of global CO2 emissions. To reduce emissions in the EU, a shift from the currently 745,000 operating public buses to electric buses (EBs) is expected in the coming years. Large-scale deployments of EBs and the electrification of bus depots will have a considerable impact on the local electric grid, potentially creating network congestion problems and spikes in the local energy load. In this work, we implement an exact, offline, modular multi-variable mixed-integer linear optimization algorithm to minimize the daily power load profile peak and optimally plan an electric bus depot. The algorithm accepts a bus depot schedule as input, and depending on the user input on optimization conditions, accounts for varying time granularity, preemption of the charging phase, vehicle-to-grid (V2G) charging capabilities and varying fleet size. The primary objective of this work is the analysis of the impact of each of these input conditions on the resulting minimized peak load. The results show that our optimization algorithm can reduce peak load by 83% on average. Time granularity and V2G have the greatest impact on peak reduction, whereas preemption and fleet splitting have the greatest impact on the computational time but an insignificant impact on peak reduction. The results bear relevance for mobility planners to account for innovative fleet management options. Depot infrastructure costs can be minimized by optimally sizing the infrastructure needs, by relying on split-fleet management or V2G options.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Multi-variable optimization; Preemption; Vehicle-to-grid (V2G)

Peer-to-peer energy trading in the real world: Market design and evaluation of the user value proposition. Proceedings of the International Conference on Information Systems - Wörner, Anselma; Ableitner, Liliane; Meeuw, Arne; Wortmann, Felix; Tiefenbeck, Verena (International Conference on Information Systems (ICIS) 2019, 2019)

Perceived algorithmic fairness: An empirical study of transparency and anthropomorphism in algorithmic recruiting - Ochmann, Jessica; Michels, Leonard; Tiefenbeck, Verena; Maier, Christian; Laumer, Sven (Information Systems Journal, 2024)
Despite constant efforts of organisations to ensure a fair and transparent personnel selection process, hiring is still characterised by systematic inequality. The potential of algorithms to produce fair and objective decision outcomes has attracted the attention of academic scholars and practitioners as a conceivable alternative to human decision-making. However, applicants do not necessarily consider an objective algorithm as fairer than a human decision maker. This study examines the conditions under which applicants perceive algorithms as fair and establishes a theoretical foundation of algorithmic fairness perceptions. We further propose and investigate transparency and anthropomorphism interventions as strategies to actively shape these fairness perceptions. In an online application scenario with eight experimental groups (N = 801), we analyse determinants for algorithmic fairness perceptions and the impact of the proposed interventions. Embedded in a stimulus-organism-response framework and drawing from organisational justice theory, our study reveals four justice dimensions (procedural, distributive, interpersonal, informational justice) that determine algorithmic fairness perceptions. The results further show that transparency and anthropomorphism interventions mainly affect dimensions of interpersonal and informational justice, highlighting the importance of algorithmic fairness perceptions as critical determinants for individual choice
Keywords: Diversity

Profitability assessment of photovoltaic battery systems based on household load profiles - Schopfer, Sandro; Tiefenbeck, Verena; Staake, Thorsten (Applied Energy, 2018)

Providing primary frequency control with residential scale photovoltaic-battery systems - Schopfer, Sandro; Tiefenbeck, Verena; Fleisch, Elgar; Staake, Thorsten (Computer Science - Research and Development, 2016)
Decentralized photovoltaic (PV) battery systems have recently received great attention from consumers around the world. PV battery systems allow consumers to reduce their dependence on the local electricity supplier at lower or equivalent costs. However, the profitability of PV battery systems depends greatly on the local meteorological conditions and the local electricity retail tariff. In central European countries, PV battery systems generate and store less electricity in winter months due to lower irradiation. The battery, in particular, can be reserved to provide ancillary services during winter months and thereby improves the overall systems economics. In this study, a large dataset consisting of individual load profiles is used to simulate a virtual power plant which provides ancillary services during battery idle times. The results show that participants with large batteries can greatly increase their overall systems economics by participating in reserve markets. However, participants with small battery capacities may not be able to recover the additional costs for communication with the virtual power plant and are thus not suitable candidates to provide grid stabilizing services (ancillary services).<br

Real-time feedback promotes energy conservation in the absence of volunteer selection bias and monetary incentives - Tiefenbeck, Verena; Wörner, Anselma; Schöb, Samuel; Fleisch, Elgar; Staake, Thorsten (Nature Energy, 2019)
Feedback interventions have proved to be effective at promoting energy conservation behaviour, and digital technologies have the potential to make interventions more powerful and scalable. In particular, real-time feedback on a specific, energy-intensive activity may induce considerable behaviour change and savings. Yet the majority of feedback studies that report large effects are conducted with opt-in samples of individuals who volunteer to participate. Here we show that real-time feedback on resource consumption during showering induces substantial energy conservation in an uninformed sample of guests at 6 hotels (265 rooms, N = 19,596 observations). The treatment effects are large (11.4% reduction in energy use), indicating that the real-time feedback induced substantial energy conservation among participants who did not opt in, and in a context where participants were not financially responsible for energy costs. We thus provide empirical evidence for real-time feedback as a scalable and cost-efficient policy instrument for fostering resource conservation among the broader public.<br

Real-time feedback reduces energy consumption among the broader public without financial incentives - Tiefenbeck, Verena; Worner, Anselma; Schoeb, Samuel; Fleisch, Elgar; Staake, Thorsten (Nature Energy, 2019)
CRIS-Team WoS Importer:2019-10-25

Real-world impact of Information Systems: the effect of seemingly small design choices - Ableitner, Liliane; Tiefenbeck, Verena; Hosseini, Sabiölla; Schöb, Samuel; Fridgen, Gilbert; Staake, Thorsten (Workshop on Information Technology and Systems (WITS), 2017)
Information system (IS) have not only become indispensable in professional contexts, but can also serve as a platform for data-based interventions targeting issues for humanity. Providing individuals with concrete feedback on their current behavior has been shown to foster sustainable behavior. So far, research on the real-world impact and underlying mechanisms of such IS-enabled interventions is scarce. In a randomized controlled field experiment with 1,423 participants, we systematically test the effect of different intervention strategies regarding their impact on energy consumption and user experience. We find a conservation effect of over 18% for the best treatment. In particular, the results suggest that small, seemingly harmless variations of IS design choices regarding numerical, normative, or emotional feedback can considerably affect behavioral outcomes (energy use). Potential explanations of observed behavior are given based on theories from psychology. The study delivers design implications for innovative IS artifacts that highlight the importance and necessity of taking cognitive processes into account. <br

Resource conservation with Green IS: A field experiment on pecuniary and non-pecuniary strategies - Ableitner, Liliane; Kupfer, Anna; Tiefenbeck, Verena; Schöb, Samuel; Staake, Thorsten (SIGGreen Pre-ICIS 2016 Workshop, 2016)

Salience, transparency, and self-nudging: a digital nudge to promote healthier food product choices - Michels, Leonard; Ochmann, Jessica; Schmitt, Kathrin; Laumer, Sven; Tiefenbeck, Verena (European Journal of Information Systems, 2023)
Information Systems (IS) research has proposed digital nudges as a promising toolset for supporting consumers in making better decisions. However, there is a vivid academic debate regarding the ethical underpinnings of nudging and potential measures to alleviate ethical concerns. One particularly promising approach to digital nudging is leveraging salience effects. Yet, the potential of digital salience nudges remains underexplored in IS literature, and little is known about how measures proposed to alleviate ethical concerns affect their behavioural impact. In a preregistered online experiment (N = 600), we assess the effects of a digital salience nudge on the healthiness of food product choices. Additionally, we examine how two proposed ethical measures, namely transparency and self-nudging, influence the nudge’s effects. We find that implementing the digital salience nudge in an online supermarket decreased the proportion of unhealthy food products chosen by 63% and increased the proportion of healthy alternatives by 30%. Notably, disclosing transparent information about the nudge did not impact its effectiveness. Offering the nudge as a self-nudge led to comparable effects to a preset nudge when combined with transparent information. We conclude that digital salience nudging is effective and that nudges can be ethically designed without compromising their behavioural impact.
Created from Fastlane, Scopus look-up
Keywords: digital nudging; ecommerce; ethics; salience; self-nudging; transparency

Self-powered water meter for direct feedback - Tasic, Vojkan; Staake, Thorsten; Stiefmeier, Thomas; Tiefenbeck, Verena; Fleisch, Elgar; Tröster, Gerhard (IEEE 2012 - 3rd International Conference on the Internet of Things (IOT 2012), 2012)
Hot water usage accounts for 16% of household demand for energy, much more than lighting and cooking (5% each) and is comparable to electricity usage for appliances (21%). As a means of helping consumers to save hot water, we present a novel self-powered water consumption sensor that enables direct consumption feedback. We equipped 91 Swiss households with the sensors and recorded 3,164 individual showers during the period of three months. The presence of feedback during a shower resulted in the reduction of average shower water consumption from 79 l to 61 l (-22.2%) per day and household. In addition to savings attributable to already installed flow restrictors, an average household could conserve 6,400 l of drinking water and 210 kWh of heat energy (projected to one year). Furthermore, we show that the effects of direct feedback on water consumption did not decline over the course of the study.<br

Shaping stable support: Leveraging digital feedback interventions to elicit socio-Political acceptance of renewable energy - Wagon, Felix; Fridgen, Gilbert; Tiefenbeck, Verena (Energy Policy, 2024)
In democratic countries, the success of energy policies hinges on citizens' support and their acceptance of policy outcomes. In this study, we develop a digital feedback intervention to prompt citizens with information that visualizes the geographical distribution of wind turbines and to evaluate the effects on socio-political acceptance. In an online experiment, we exposed 430 German citizens to a personalized digital feedback intervention and elicited their acceptance of renewable wind energy. The results are threefold: First, citizens' acceptance of renewable wind energy that results from digital feedback is lower than initially claimed. Second, citizens who meaningfully engage with the digital feedback intervention are more likely to revise their acceptance of wind energy. Third, and surprisingly, citizens’ ecological attitude and place attachment to their current residence had no significant effect on the extent to which they revised their acceptance of renewable wind energy. Our results demonstrate that digital feedback interventions can act as a “sensor” for socio-political acceptance. This contributes to informing citizens about energy policy outcomes and provides valuable insights for policymakers promoting a participatory democracy paradigm.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Citizen engagement; Digital feedback intervention; Online experiment; Renewable energy; Socio-political acceptance

Short-term spark or sustained impact? Investigating the long-term effect of real-time feedback - Tasic, Vojkan; Tiefenbeck, Verena; Schöb, Samuel; Staake, Thorsten (European Conference on Information Systems (ECIS 2015), 2015)
In order to adopt sustainable practices and strategies, organizations and individuals need to understand the environmental impact of their behavior and the knowledge about successful resource conservation strategies. Information Systems research and real-time feedback systems in particular can help to bridge this "environmental literacy gap”. In previous work, we presented an IS artifact that presents consumers with behavior-specific information on their energy and water consumption in real time. We found that this approach reduces energy and water consumption by 22%. In this work-inprogress paper, we address the open question of effect persistence in the long term. We analyze 17,612 data points collected in a 12-month field study from 50 households. First analyses indicate that the effect remains stable over time. In line with literature on “data push” systems, we argue that feedback systems should not require an additional step of user action to access the feedback which may be a barrier to longer effect persistence of information systems.<br

Solar PV sharing in urban energy communities: Impact of community configurations on profitability, autonomy and the electric grid - Mehta, Prakhar; Tiefenbeck, Verena (Sustainable Cities and Society, 2022)
Through a deterministic techno-economic analysis based on high-resolution real-world demand data from 3,594 households, we analyse how the configuration of a solar energy community (EC) impacts its economic and technical performance. We find that prosumer ratio and PV capacity, but not community size, affect prosumer profitability and EC self-sufficiency rate (SSR). The profitable prosumer share in an EC falls below 25% as the prosumer ratio increases beyond 30% for PV systems sized to meet annual demand (M-sized), and 50%, respectively, for systems sized to meet twice the annual demand (L-sized) due to economies of scale. The SSR steadily increases with prosumer ratio and PV capacity to a maximum of 37.8%. However, all three EC design dimensions influence the grid impact. In the absence of energy storage, this imposes a permissible range on the prosumer ratio to avoid grid upgrades – 60-100% and 30-50% for M- and L-sized systems, respectively, which in turn limits the SSR to 29.4-33.3% and 28.2-33.1%. The results establish clear configurations that strike a good balance between different performance metrics of an EC. EC planners, policymakers, and grid operators can build on these results as rules of thumb to incentivize EC formation while maximizing welfare for all stakeholders.
CRIS-Team Scopus Importer:2022-10-07
Keywords: Community configuration; Energy community; Production-to-demand ratio; Profitability; Prosumer ratio; Self-sufficiency

Supporting Citizens’ Political Decision-Making Using Information Visualisation - Graf, Vanessa; Graf-Drasch, Valerie; Tiefenbeck, Verena; Weitzel, Robin; Fridgen, Gilbert (In Proceedings of the 28th European Conference on Information Systems (ECIS), 2020)
Individual decision-making is a complex process. If carried out by individual citizens in the context of politically relevant decisions, serious consequences at all levels of a society might occur. That is why these decisions need to be made with care and preferably on a broad set of information to reflect citizens’ true preferences. However, due to limited attention, citizens often consider only salient aspects in their decision-making. To mitigate unwanted consequences following therefrom, citizens are in dire need of decision-support. We address this need by developing an Information Systems (IS) tool. Being based on information visualisation, our tool supports citizens by providing instant feedback. To ensure a meaningful engagement, the IS tool is designed according to gamification principles. A first instantiation in the context of renewable energy acceptance in Germany yields three key findings: First, we find indications that young, urban, and environmentally aware citizens are willing to accept a high percentage of renewable wind energy. Second, we find that the tool influences citizens’ decision-making. Third, we find citizens to update, however not completely turn over their preferred level of renewable wind energy after interaction with the tool. This holds true across different cross-sections of the population. <br
Keywords: Decision-Making; Decision-Support; Citizens; Information Visualisation; Live-Feedback; Renewable Energy; Wind Turbine Acceptance; Gamification

Switching Off: Energy Saving Goals Outshine Incentives—Evidence from a Field Experiment - Borzino, Natalia; Hiepler, Benjamin; Schmitt, Kathrin; Schmitz, Jan; Schubert, Renate; Tiefenbeck, Verena (Environmental & Resource Economics, 2025)
Feedback interventions are a promising tool for promoting household energy conservation and addressing climate change. This study examines whether their effectiveness improves with incentivized energy saving goals through a field experiment involving 422 Singa- porean households over eight months. All treatment groups received tailored feedback reports, energy saving goals, and tips. Two groups also received additional incentives: monetary rewards or environmental donations. Households receiving only feedback, goals and savings tips reduced electricity use by 16% compared to the control group, but those offered additional monetary or environmental incentives achieved no further savings. No- tabl the effects persisted marginally post-intervention in the goal treatment. These results indicate that low-cost behavioral strategies like feedback, savings tips and goal setting can be as effective as costly incentives, providing a scalable and economical pathway for energy conservation initiatives.<br
CRIS-Team Scopus Importer:2025-04-11
Keywords: Energy conservation · Incentives · Feedback · Goal-setting · Field experiment

Taking mental health & well-being to the streets: An exploratory evaluation of in-vehicle interventions in the field - Koch, Kevin; Tiefenbeck, Verena; Liu, Shu; Fleisch, Elgar; Wortmann, Felix (ACM CHI Conference on Human Factors in Computing Systems, 2021)

Technology adoption vs. continuous usage intention: Do decision criteria change when using a technology? - Kupfer, Anna; Ableitner, Liliane; Schöb, Samuel; Tiefenbeck, Verena (Americas Conference on Information Systems (AMCIS 2016), 2016)
Various models in Information Systems (IS) research seek to understand why individuals embrace or resist the adoption or use of a technology. Different models analyze the factors shaping user intentions at different stages of technology adoption and use. Yet, less is known how the factors shaping adoption intention subsequently evolve into continuous usage intention as users become (more) familiar with the technology. This paper investigates participants’ (N=549) adoption and continuous usage intention of a smartphone application for energy efficiency twice: at two different stages of experience, but for the same technology, in the same setting, and in particular with the same sample. In both cases, we use the Unified Theory of Acceptance and Use of Technology (UTAUT1&2). While UTAUT explains adoption intention well, we find only moderate support for continuous usage intention. In line with prior research, our data suggests that beliefs are updated from adoption to continuous usage stage.<br

The Acceptance of AI-based Recommendations: An Elaboration Likelihood Perspective - Michels, Leonard; Ochmann, Jessica; Tiefenbeck, Verena; Laumer, Sven (17. Internationale Tagung Wirtschaftsinformatik, 2022)

The ambiguous boundary between professional and private use of information systems: a bibliometric analysis - Kupfer, Anna; Tiefenbeck, Verena; Staake, Thorsten (European Conference on Information Systems (ECIS 2018), 2018)
Traditionally, Information Systems (IS) research focuses on the use and development of IS within and between organizations. This lens dates back to when IS use was mostly confined to professional contexts. Over the last decades, the application of IS has experienced a strong expansion to private contexts, where a large share of IS investments, increase in computing power, and interaction with IS – in the form of PCs, smartphones, tablets, wearables, etc. – takes place today. Senior scholars have highlighted the need to acknowledge the relevance of private contexts for theory building and to redefine the intellectual core of IS. Therefore, we conducted a bibliometric analysis of the entire set of articles (n=737) published in the top IS outlets for the years 1995, 2005, and 2015. The results suggest that the share of articles focusing on the private context is still small, yet, it has quintupled (from 2 to 10 %) in the past twenty years. Moreover, 11% of the articles analyzed investigate topics that involve both professional and private contexts. The findings contribute to the general discussion on boundaries and trends in IS research and serve as motivation in particular for scholars conducting research on the private use of IS. <br

The behavioral response to a corporate carbon offset program: A field experiment on adverse effects and mitigation strategies - Günther, Sebastian A.; Staake, Thorsten; Schöb, Samuel; Tiefenbeck, Verena (Global Environmental Change-Human and Policy Dimensions, 2020)
More and more organizations are compensating the greenhouse gas emissions caused by their products and services through carbon offset programs. From the customers’ perspective, the mitigation of negative externalities associated with their demand may increase the utility derived from the (then guilt-free) consumption. In particular in settings where consumers do not pay for the marginal cost of consumption, this may lead to higher levels of resource use. This article empirically examines how the announcement of an organizational carbon offset program affects consumption in a CO2-intensive everyday activity (showering). We further evaluate the provision of real-time feedback as a strategy to counteract potential increases in consumption. For this purpose, we conducted an eight-week randomized controlled natural field experiment in a German youth hostel (full 2 × 2 factorial design; N = 9,999 observations). Consumption in the group with the offset program was statistically significantly higher than in the control group (by 5.4 to 15.5%). However, participants who additionally received real-time feedback on their consumption did not increase their resource use compared to the control group. While the results suggest that carbon offset programs may increase resource use, the findings provide evidence that organizations can counteract these adverse effects by making the individual's resource use salient.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Behavioral rebound; Carbon offsets; CO; Corporate social responsibility; Natural field experiment; Resource consumption

The effects of real-time feedback on resource consumption in single- and multi-person households - Tiefenbeck, Verena; Tasic, Vojkan; Staake, Thorsten (Swiss Society of Economics and Statistics, Annual Congress 2013: „The Energy Transition and its Challenges”, 2013)

The impact of numerical vs. symbolic eco-driving feedback on fuel consumption – a randomized control field trial - Dahlinger, André; Tiefenbeck, Verena; Ryder, Benjamin; Gahr, Bernhard; Fleisch, Elgar; Wortmann, Felix (Transportation Research Part D-Transport and Environment, 2018)
Despite the fact that more and more car dashboards are being equipped with powerful, high-resolution displays, allowing for radically new ways to design driving feedback, the question of what impact different design types and features have on real-world eco-driving remains largely unclear. To address this research gap, we conducted a randomized control field trial in Switzerland with 62 road assistance drivers over a period of 10 weeks, covering over 245,000 km. We evaluate the effect of eco-driving feedback on fuel consumption for two types of feedback: numerical feedback (which uses numbers and gauges to present numerical values) and symbolic feedback (which translates numerical values into symbolic representations). Both, numeric and symbolic eco-driving feedback were tested against a control group. Data analyses are performed on the level of 265,939 dynamic road segments with constant road characteristics to account for the significant effect of road attributes on fuel consumption. Results of a fixed-effects regression models reveal that only the symbolic feedback design led to significant reductions of 2–3% in fuel consumption. The effect is robust across different model specifications that control for the influence of road attributes and other covariates. We conclude that the design of eco-driving feedback can have a significant impact on its effectiveness for promoting a less fuel-consuming driving style. We conjecture that there is a large untapped potential for manufacturers to use modern digitalized dashboards that can improve the impact of driver feedback systems.<br
Keywords: Eco-driving; Real-time feedback; Feedback design; Field experiment; Real-world driving

The Impact of Transparency in AI Systems on Users’ Data-Sharing Intentions: A Scenario-Based Experiment - Rosenberger, Julian; Kuhlemann, Sophie; Tiefenbeck, Verena; Kraus, Mathias; Zschech, Patrick (19. Internationale Tagung Wirtschaftsinformatik, 2024)

The influence of algorithm aversion and anthropomorphic agent design on the acceptance of AI-based job recommendations - Ochmann, Jessica; Michels, Leonard; Zilker, Sandra; Tiefenbeck, Verena; Laumer, Sven (Proceedings of the 41st International Conference on Information Systems (ICIS), 2020)

The role of self-set goals in IS-enabled behavior change - Wörner, Anselma; Tiefenbeck, Verena (European Conference on Information Systems (ECIS 2018), 2018)
IS-enabled feedback interventions and self-tracking devices have shown to successfully induce behavior change in various professional and private domains. However, in particular for private contexts, the mechanisms that govern these processes are not well understood. Based on goal-setting theory, we identify self-set goals as a potential driver of behavior change induced by IS-enabled feedback. In a two-month field study, we provide activity-specific real-time feedback on resource consumption to 413 households and study the formation of self-set resource conservation goals in response. We chose showering as an example of an energy-intensive, habitual low-involvement target activity. The results suggest that IS-enabled real-time feedback successfully induces most individuals to set themselves a goal without exhortation, even for this kind of low-involvement activity. Against the predictions of goal-setting theory, we find that individuals tend to set themselves ambitious goals. In line with goalsetting theory, individuals who set themselves ambitious goals conserve more resources. Given the difficulty of defining adequate goals externally, and the risk of goal rejection and adverse reactions associated with externally assigned goals, the results suggest that personal IS should encourage users to self-set goals.<br

The role of the user in peer-to-peer energy communities - Ableitner, Liliane; Schopfer, Sandro; Tiefenbeck, Verena (5th European Conference on Behaviour and Energy Efficiency (Behave 2018), 2018)

The uncertain path from good intentions to actual behavior: A field study on mobile app usage - Tiefenbeck, Verena; Kupfer, Anna; Ableitner, Liliane; Schöb, Samuel; Fleisch, Elgar; Staake, Thorsten (Twenty-First DIGIT Workshop, 2016)
In the domain of energy consumption, good intentions do not necessarily imply sustainable behavior. Information Systems (IS) can promote energy efficiency by providing users with information about their behavior. While IS research has developed several models explaining adoption and usage of various technologies in the organizational context, less is known about the adoption of IS in the consumer context. We examine usage behavior of a sustainability smartphone application in a large-scale field study applying the Unified Theory of Acceptance and Use of Technology (UTAUT). Our data, collected in two surveys and from server log data, suggests that users do not follow through on their good intentions: while intention is indeed well explained by UTAUT factors, it does not necessarily predict usage. Moreover, we find only a mild correlation of self-reported usage and log data. The results highlight the need to better understand adoption and usage of I

Towards a measurement scale for self-tracking: Attitudes and user characteristics - Kupfer, Anna; Kehr, Flavius; Tiefenbeck, Verena (European Conference on Information Systems (ECIS 2016), 2016)
Self-tracking, or the desire to quantify one’s own behaviour by means of personal information systems, has developed from a niche activity for early adopters to a mass phenomenon. Despite its increasing spread in society, however, little is known about the drivers of technology adoption and use in this specific domain. Addressing this gap, the research-in-progress at hand aims to (1) theorize on the role of self-tracking attitudes – defined as specific consumer attitudes in the self-tracking context, and (2) present a research plan with the goal of developing a self-report scale capable to measure selftracking attitudes. We present the results of a first literature review and of 24 explorative expert interviews conducted to identify relevant cognitive, affective and conative concepts related to self-tracking attitudes. The results constitute a first step to develop a measurement scale that aims to contribute to adoption research and the development of successful self-tracking systems.<br

Trading solar energy within the neighborhood: Field implementation of a blockchain-based electricity market - Wörner, Anselma; Ableitner, Liliane; Meeuw, Arne; Wortmann, Felix; Tiefenbeck, Verena (8th DACH+ Conference on Energy Informatics, 2019)
Due to environmental and resiliency benefits, distributed energy resources (DER) are a potential solution for meeting future electricity demand, but their integration into centralized power markets on the large scale is challenging. Many practitioners argue that blockchain technology can create new market structures for DER like local peer-to-peer energy markets which foster renewable generation. To get an understanding of the status quo of the research on blockchain-based energy exchange, we conducted a systematic literature review on the existing academic articles and industry projects. This article describes the design and technical specifications of the first real blockchain-based electricity market in Switzerland derived from this literature review and outlines the implementation of this market in the real world. The findings provide valuable guidelines for the integration of DER into future sustainable energy markets.<br

Transparency in design science research - Hevner, Alan R.; Parsons, Jeffrey; Brendel, Alfred Benedikt; Lukyanenko, Roman; Tiefenbeck, Verena; Tremblay, Monica Chiarini; vom Brocke, Jan (Decision Support Systems, 2024)
Research transparency promotes openness and trust in the process, evidence, contributions, and implications of scientific inquiry. Information Systems (IS), as a pluralistic research community, must address transparency in relation to its use of multiple research methods appropriate to complex socio-technical contexts and challenging research questions. This commentary presents a set of important transparency challenges and actionable guidance for the Design Science Research (DSR) community. We propose a DSR Transparency Framework containing six forms of transparency: process, problem space, solution space, build, evaluation, and contribution. For each, we discuss challenges with guidance to achieve effective DSR transparency throughout the publication process.
CRIS-Team Scopus Importer:2024-05-17
Keywords: Design science research; Open design; Research transparency

Untersuchung des Selbstversorgungsgrades und der Wirtschaftlichkeit von PV-Batteriesystemen anhand eines grossen Smart-Meter-Datensatzes - Schopfer, Sandro; Tiefenbeck, Verena; Staake, Thorsten (14. Symposium Energieinnovation 2016, 2016)
Fortschritte in der Batterietechnologie und sich ändernde Einspeisevergütungen für Photovoltaikanlagen (PV) steigern die Attraktivität einer Eigenversorgung für Privathaushalte. Die ambitionierten Pläne von Lösungsanbietern wie Tesla, Sonnenbatterie, ABB u.a. lassen bereits mittelfristig eine wachsende Anzahl von PVBatterie-Systemen erwarten. Im Rahmen dieses Beitrags wird der Selbstversorgungsgrad mit Hilfe echter Haushaltslastprofile für verschiedene PV- und Batteriekonfigurationen ermittelt und die Wirtschaftlichkeit für unterschiedliche Haushaltstypen in Abhängigkeit von deren Lastprofilen abgeleitet. Es zeigt sich, dass zwar eine Grosszahl von PV-Batterieanlagen auch ohne Subventionen (Cash-Boni und/oder Einspeisevergütungen) wirtschaftlich betrieben werden kann, allerdings mit relativ niedrigen Selbstversorgungsgraden.<br

User behavior in a real-world peer-to-peer electricity market - Ableitner, Liliane; Tiefenbeck, Verena; Meeuw, Arne; Wörner, Anselma; Fleisch, Elgar; Wortmann, Felix (Applied Energy, 2020)
Peer-to-peer (P2P) energy markets are a widely discussed approach toward a sustainable energy supply that allows private owners of distributed energy resources (e.g., solar panels) and consuming households to trade energy directly without intermediaries. P2P energy markets are expected to contribute to a green, local, and fair energy system in the future. The approach implies a paradigm shift regarding the role of citizens who evolve from passive consumers into active market participants. While first existing research primarily focused on the technical feasibility of such scenarios, end users and their role in P2P markets have received little attention. The present article studies the behavior of 35 households and two commercial entities in Switzerland's first real-world P2P energy market. In this unique real-world setting, based on a mixed methods approach, we developed and deployed a web application and empirically studied interaction, acceptance, and participation in electricity pricing in this P2P energy market, using data from system logs, surveys, and interviews. The findings are threefold. First, the P2P energy market was well received among its users, indicated by comparably high and stable usage activity of the web application throughout the study (4.5 months). Second, users in the sample are heterogeneous; based on their engagement with the web application and their stated preferences, they can be categorized into those who want to actively set prices (30%); those who prefer automated prices determined by an information system (35%); and non-users/non-respondents to surveys (35%). Third, an analysis of interviews with nine households suggests that P2P energy markets may increase the salience of renewable energies and may promote load-shifting activities. Thus, the article provides empirical insights about the user behavior of households and their future role in decentralized energy scenarios.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Blockchain; Distributed energy resources; Peer-to-peer energy market; Price setting; User behavior; Web application